Comparative Evaluation of Second-Class Lever Principle Based Single-Axis Solar Tracking System and Conventional System - Kumba, Krishna; Simon, Sishaj P.; Sundareswaran, Kinattingal; Nayak, Panugothu Srinivasan Rao (Distributed Generation & Alternative Energy Journal, 2023)
This article presented the comparative study of the second-class lever principle single-axis solar tracking system (SCLPSAST) with the fixed solar axis (FSA) system. The SCLPSAST system continuously tracks the sun regardless of atmospheric conditions from sunrise to sunset. This SCLPSAST system is a cost effective and straightforward solar tracking system built with negligible operational costs. The Photovoltaic (PV) panel are directed towards the sun throughout the year without using any additional power. The main advantage is that an external motor is not required to control the solar panel. A detailed performance evaluation of the SCLPSAST system is carried out for 90 days (from Jan 2022 to Mar 2022) with the FSA system. Finally, the working functionality, efficiency improvement, and experimental consequences of the SCLPSAST system are detailed. SCLPSAST and the fixed solar system generated 8.92 kWh and 7.03 kWh, respectively, which is around 26.87% more energy than the FSA system.